The Characteristic Features of Educational Work with the Student in the Residential Areas in the South of Ukraine in the Second Part of XX- th Century - Alona Halysheva (Pedagogical Discourse, 2015)
In the article the author analyzes the definition of educational work with the students in the residential areas due to the specific historical period. The author gives the results of researches of the leading scientists and educators as to the studying this problem. The author gives the detailed review of the most characteristic features of educational work with the students in the residential areas in the south of Ukraine in the second part of XX – th century) basing on the researches of the scientists. In this article the author presents the main directions of the organization of the free time of the children and teenagers. The article shows the topicality and the importance of the problem. The facts which were provided confirmed the need to involve the students into the after-classes activities in their free time for their self-education and vital self-determination.The main feature of this article consists in considering the historical material due to the problem of educational work with the students in the residential area in the south of Ukraine, in Melitopol in the second part of the XX century. The article is about the education and educational work with the students in their residential areas. It presents different views and analysis of recent researches of the well-known educators about the definition of the term «education». Basing on the researches of the scientists and leading educators the author gives detailed analysis of this problem in the article. The article shows that nowadays it is important to involve the students into the active types of the after – classes activities in their free time for their self-education and vital self-determination.